2012
DOI: 10.1186/1476-9255-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of the toll like receptors 2 and 4 in obese individuals: its significance for obesity-induced inflammation

Abstract: BackgroundExpression profile of the toll like receptors (TLRs) on PBMCs is central to the regulation of proinflammatory markers. An imbalance in the TLRs expression may lead to several types of inflammatory disorders. Furthermore, the dynamic regulation of inflammatory activity and associated impaired production of cytokines by peripheral blood mononuclear cells (PBMCs) in obese individulas remain poorly understood. Therefore, we determined the perturbation in TLRs (TLR2 and TLR4), their adaptor proteins (MyD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 35 publications
(31 reference statements)
13
109
4
3
Order By: Relevance
“…19 Similarly, Ahmad et al also found a significantly increased expression of TLR2, TLR4, and MYD88 in both peripheral blood mononuclear cells and subcutaneous adipose tissue of obese and overweight subjects compared to lean controls. 20 In agreement with these reports, we detected a significant correlation between the gene expression of TLR4 in subcutaneous fat with the subcutaneous and visceral expression of MYD88. In addition, we detected a significant correlation between the subcutaneous and visceral expression of MYD88 with the expression of PAI-1 in both adipose tissues.…”
Section: Figsupporting
confidence: 81%
“…19 Similarly, Ahmad et al also found a significantly increased expression of TLR2, TLR4, and MYD88 in both peripheral blood mononuclear cells and subcutaneous adipose tissue of obese and overweight subjects compared to lean controls. 20 In agreement with these reports, we detected a significant correlation between the gene expression of TLR4 in subcutaneous fat with the subcutaneous and visceral expression of MYD88. In addition, we detected a significant correlation between the subcutaneous and visceral expression of MYD88 with the expression of PAI-1 in both adipose tissues.…”
Section: Figsupporting
confidence: 81%
“…TLR2 and TLR4 expression and activation are increased in bone marrow-derived macrophages of non-obese diabetic (NOD) mice, correlating with increased NF-κB activation and increased pro-inflammatory cytokines [33] . A clinical study showed that TLR2/4 mediated inflammation in monocytes was significantly correlated to the HbA1c levels in diabetic patients [34] . Furthermore, TLR4 has been reported to link the inflammatory responses of diabetes and periodontitis.…”
Section: Wwwchinapharcom Zhen L Et Almentioning
confidence: 99%
“…Certain TLRs are known to be involved in metabolic inflammation, especially, the TLR4 has emerged as a metabolic sensor of lipopolysaccharide (LPS) as well as saturated free fatty acids (sFFAs) that are abundantly found in obese/T2D individuals [10]. Modulations in the expression of TLR1, TLR2, TLR4, TLR5, TLR6, TLR7, TLR8, and TLR9 have been reported in obesity and T2D [11-14]. Importantly, metabolic disease associated changes in the adipose tissue expression of TLR10 have remained unclear.…”
Section: Introductionmentioning
confidence: 99%